Prevalence of Gastroesophageal Reflux in Infants with Recurrent Brief Apneic Episodes - Shahid Sheikh; Thomas C Stephen; Barbara Sisson (Canadian Respiratory Journal)
BACKGROUND: Apnea in an infant can be a diagnostic dilemma for the treating pediatrician. It is suggested that in some infants, gastroesophageal reflux (GER) might be a factor in the pathogenesis of apnea, although its role as a cause of apnea is still controversial.